Immunohistochemical study of p-53 protein expression in chronic lymphocytic leukemia and its correlation with clinicopathological factors - Abdullah, Abdulrazzaq W.; Jaafar, Abdulkareem M.; ALsaadawi, Adel R. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: several factors render chronic lymphocytic leukemia an interesting subject for study by researchers. These include marked progress in understanding the molecular biology of normal and neoplastic lymphoid cells and recent advances in molecular genetics techniques. Among molecular markers, p-53 cancer suppressor gene has been widely studied. Objectives: is to correlate p-53 protein expression in chronic lymphocytic leukemia, as examined by immunohistochemical method, with some pathological and clinical parameters. Patients and methods: this is a retrospective study; whereby archival paraffin-embedded bone marrow tissue blocks along with the clinical and hematological records of fifty patients (35 males and 15 females), with chronic lymphocytic leukemia and twenty cases as control were obtained from the Department of Hematology of the Medical City Teaching Laboratories in the period from April 2012 to April 2014. P-53 was studied by immunohistochemical staining. Results: the frequency of p53 positive patients in the study group was 16% (8 of 60 cases). Patients with high score for p-53 were more frequently and significantly associated with high-risk clinical stage than patients with low score. There was a significant direct positive correlation between increasing scores of p53-positive chronic lymphocytic leukemia cells and advancing clinical stage of the disease. Conclusion: although p53 alteration may occur early in the course of the disease, as shown by the p53 positivity in a proportion of patients in low and intermediate-risk stage of the disease, the highest frequency p53-positive cells, has been observed in high-risk stage of the disease.